2011
DOI: 10.1039/c0ob00479k
|View full text |Cite
|
Sign up to set email alerts
|

Interproton distance determinations by NOE – surprising accuracy and precision in a rigid organic molecule

Abstract: The accuracy inherent in the measurement of interproton distances in small molecules by nuclear Overhauser enhancement (NOE) and rotational Overhauser enhancement (ROE) methods is investigated with the rigid model compound strychnine. The results suggest that interproton distances can be established with a remarkable level of accuracy, within a few percent of their true values, using a straight-forward data analysis method if experiments are conducted under conditions that support the initial rate approximatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
138
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 10 publications
8
138
0
4
Order By: Relevance
“…Stereospecific assignments for all nondegenerate diastereotopic pairs of protons were determined from coupling constant analysis and NOESY cross peak intensities. Our assignments for the free base in CDCl 3 agree with stereospecific assignments reported previously by others [6,[13][14][15] for this sample and solvent. We note that names given to protons in some pairs of diastereotopic protons among these previous reports have been inconsistent and have followed the naming convention used by Thiele.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Stereospecific assignments for all nondegenerate diastereotopic pairs of protons were determined from coupling constant analysis and NOESY cross peak intensities. Our assignments for the free base in CDCl 3 agree with stereospecific assignments reported previously by others [6,[13][14][15] for this sample and solvent. We note that names given to protons in some pairs of diastereotopic protons among these previous reports have been inconsistent and have followed the naming convention used by Thiele.…”
Section: Resultssupporting
confidence: 91%
“…[5] It is a favored standard sample for NMR spectroscopy because of its availability, low cost, and the remarkable chemical shift dispersion of its 22 proton resonances. [6] Strychnine is usually obtained by acid-base extraction from seeds of the Strychnos nux vomica tree commonly grown in India. In addition to the neutral compound, more than a dozen different salts of the protonated amine (strychninium cation) have been described, [7] and many are commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…However, NOEs at 284 K show a better correlation with the Xray structure which may be caused by the fact that the NMR restraints for the bundle were measured at 298 K [165,167]. Subsequently, Butts et al showed the method yields very accurate distances (within a few percent of the true values) for rigid organic molecules as examplified on the model compound strychnine [172]. 1D and 2D NOESY experiments were conducted with 500 ms mixing times.…”
Section: Validation Of Experimental Distancesmentioning
confidence: 99%
“…In fact, a very similar UPy−urethane interaction has recently been reported for the crystal structure of the dimeric cycle of a related UPy compound. 21 As elegantly demonstrated by Butts et al for strychnine, 22 analysis of NOESY data can be used to accurately estimate proton−proton distances. A similar analysis in our case reveals that the distance between protons H i −H a (Figure 1 and Figure S9) is 110% of the distance between protons H i −H h , a value that is in close agreement with typical distances (111%) obtained by molecular modeling.…”
mentioning
confidence: 99%